Percepções ambientais sobre a madeira: usos e significados no polo madeireiro de Itacoatiara - AM - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Wood is a natural resource that has been used by humans since their emancipation from nature and when they started to handle it. The wood was present throughout the evolutionary process of human civilizations as the basic element used for a range of activities. The established relationship between person and object (wood) structures and shapes subjectivities that must be studied in order to understand the people s view about reality and how they fit into it. Thus, the present study investigated the environmental perceptions about wood of forty people in Itacoatiara, where twenty of those have a direct relationship with the wood and the other twenty have indirect relation. The overall objective was to analyze the perception of residents from Itacoatiara - AM about wood, uses and sociocultural meanings in the context of environmental issues . The specific objectives were to characterize different types of social uses of wood in the daily lives of people in their different roles, identify the motivations of consumption and use of wood and check what are the meanings and values atributed to wood as a natural resource. The methodology of data collection was the semi-structured interview. Subsequently, the interviews were transcribed and passed through a content analysis. The results allowed us to suggest that the social use of wood is more related to the residential space than with the workspace, except those in which the wood is used as the main object of work. The motivations of consumption are related to the material characteristics of wood with emphasis on durability. The survey also revealed that the timber has three evident major social meanings: as a material that define identity antagonisms within two social groups (those who say working with wood and those who say they have the right to work with wood), as a material with a lot of distinctions, especially because of their material characteristics, and as a material whatsoever, exempt of distinctions. The meanings of the timber shown in this study offer the possibility of understanding a very peculiar reality, experienced and perceived by people directly and indirectly involved with the wood. These understandings can serve as a basis for developing more effective public policies for access and use of this so necessary natural resource which is being handled by mankind from the beginning.
Keywords: Percepção Ambiental; Madeira; Identidades Sociais; Environmental Perception; Wood; Social Identities; CIÊNCIAS AGRÁRIAS